Methodology and features of assessing the economic effect of implementing digital educational environment models in secondary vocational and higher education systems - Fedotov, Alexander V.; Polushkina, Elena A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2021)
Problem and goal. The active introduction of e-learning and distance learning technologies in the educational process, the reform of traditional models of learning and education have become priority areas of reforms and initiatives in various national education systems in the 21st century. Given that public spending is the main source of funding for education in the OECD countries, assessing the economic impact of implementing a digital educational environment at different levels of education under pressure on public budgets has become a key issue for national governments and educational organizations, as well as the subject of special research. In Russian practice assessment of the economic effect of the full-scale use of e-learning and distance learning technologies in the implementation of educational programs of secondary professional (training of middle-level specialists) and higher education have not yet been carried out. For these purposes, a methodology has been developed, which, however, needs to be tested. Results. The study identified a list of costs required to ensure the full use of e-learning and distance educational technologies in realization of educational programs of secondary vocational (training of mid-level professionals) and higher (including graduate school) education; the methodlogy for assessing the economic effect of these measures is justified, and calculations are made based on this methodology. Conclusion. The developed methodology has shown its effectiveness and needs further research and quantitative analysis.